TUPE: A PEOPLE DETAINED IN TIME - Vetter Parodi, Luisa (2008)
Tupe is located at the drainage of Cañete River, Department of Lima, Peru. Most of its pre-Columbian history remains unknown even though there are many archaeological sites surrounding it. Its language (jaqaru) and traditional dress have been preserved. One of the most distinctive features of clothing is the use of tupus or prehispanic pins which were thought to be lost in nineteenth century.